2018
DOI: 10.1001/jamapediatrics.2018.0249
|View full text |Cite
|
Sign up to set email alerts
|

Association of Temporal Changes in Gestational Age With Perinatal Mortality in the United States, 2007-2015

Abstract: IMPORTANCE Whether the changing gestational age distribution in the United States since 2005 has affected perinatal mortality remains unknown. OBJECTIVE To examine changes in gestational age distribution and gestational age-specific perinatal mortality. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study examined trends in US perinatal mortality by linking live birth and infant death data among more than 35 million singleton births from January 1, 2007, through December 31, 2015. EXPOSURES Year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 53 publications
2
31
2
Order By: Relevance
“…28 In parallel, rates of stillbirths increased. 29 The present study showed a survival rate of 77% among all live-born infants at 22-26 weeks' gestational age in 2014-2016, and the stillbirth rate was found to be significantly lower than the rate reported in the rest of Europe. 30 Systematic survival among infants at 22 weeks' gestational age has not been restricted to Swedish hospitals.…”
Section: Discussioncontrasting
confidence: 50%
“…28 In parallel, rates of stillbirths increased. 29 The present study showed a survival rate of 77% among all live-born infants at 22-26 weeks' gestational age in 2014-2016, and the stillbirth rate was found to be significantly lower than the rate reported in the rest of Europe. 30 Systematic survival among infants at 22 weeks' gestational age has not been restricted to Swedish hospitals.…”
Section: Discussioncontrasting
confidence: 50%
“…4) [68]. Whereas this proportion shows declines over that 13-year span in the USA, a recent study revealed that neonatal mortality increased for singleton late preterm and early term births between 2007 and 2015 after adjustment for population characteristics [37]. The authors' interpretation is that declining preterm and early term birth rates, resulting from policies to stop non-medically indicated deliveries, is leading to higher-risk babies being born at these gestational ages.…”
Section: Infant Outcomes Associated With Late Preterm and Early Term mentioning
confidence: 95%
“…The rise was largely accounted for by increases in late preterm births [6], as well as indicated deliveries [12,35]. Rates in the USA then began to decrease when indicated preterm deliveries declined by 17.2% (from 3.9% to 3.2%) between 2005 and 2012 [36] and overall late preterm singleton live births declined from 6.4% to 5.8% between 2007 and 2015 [37]. In Europe, many European countries maintained or reduced their rate of singleton preterm birth [22].…”
Section: Prevalence Of Late Preterm and Early Term Birthsmentioning
confidence: 99%
“…[9][10][11] A recent study showed that, among singleton births in the United States, births at late preterm (34-36 weeks), early term (38-39 weeks), and postterm (42-44 weeks) gestations declined between 2007 and 2015. 12 However, perinatal mortality rates at these gestations increased by 1% to 4% annually. In contrast, births at term gestations (39-40 weeks) increased, but mortality rates at this gestation decreased by 1.5%.…”
mentioning
confidence: 99%